The Effect of Orally Administered Dronabinol on Optic Nerve Head Blood Flow in Healthy Subjects—A Randomized Clinical Trial. Issue 1 (23rd February 2020) - Hommer, Nikolaus; Kallab, Martin; Szegedi, Stephan; Puchner, Stefan; Stjepanek, Kristina; Bauer, Martin; Werkmeister, René M.; Schmetterer, Leopold; Abensperg‐Traun, Marihan; Garhöfer, Gerhard; Schmidl, Doreen
Abstract : It has been hypothesized that besides its intraocular pressure (IOP) lowering potential, tetrahydrocannabinol (THC) may also improve ocular hemodynamics. The aim of the present study was to investigate whether single oral administration of dronabinol, a synthetic THC, alters optic nerve head blood flow (ONHBF) and its regulation in healthy subjects. The study was carried out in a randomized, placebo‐controlled, double‐masked, two‐way crossover design in 24 healthy subjects. For each study participant, 2 study days were scheduled, on which they either received capsules containing 5 mg dronabinol or placebo. ONHBF was measured with laser Doppler flowmetry at rest and while the study participants performed isometric exercise for 6 minutes to increase mean arterial blood pressure (MAP). This was repeated 1 hour after drug intake. Ocular perfusion pressure (OPP) was calculated as 2/3MAP–IOP. Dronabinol was well tolerated and no cannabinoid‐related psychoactive effects were reported. Neither administration of dronabinol nor placebo had an effect on IOP, MAP, or OPP. In contrast, dronabinol significantly increased ONHBF at rest by 9.5 ± 8.1%, whereas placebo did not show a change in ONHBF (0.3 ± 7.4% vs. baseline, P  < 0.001 between study days). Dronabinol did not alter the autoregulatory response of ONHBF to isometric exercise. In conclusion, the present data indicate that low‐dose dronabinol increases ONHBF in healthy subjects without affecting IOP, OPP, or inducing psychoactive side effects. In addition, dronabinol does not alter the autoregulatory response of ONHBF to an experimental increase in OPP. Further studies are needed to investigate whether this effect can also be observed in patients with glaucoma.